(untitled) (Research, Society and Development, 2021)
Membrane can be defined as a barrier, separating two phases and restricts the transport of various chemicals selectively, showing different classifications, morphologies, and geometries. These materials are used in applications such as: ultrafiltration, microfiltration, pervaporation, gas separation, artificial organs and other medical purposes. Hollow fiber synthetic membranes obtained from different types of materials have been gaining a great attention in last decade because the advantages in relation to its large area available of the membranes and the greater compactness relative flat and tubular membranes used in the various membrane separation processes. Hollow fibers are mostly prepared by the phase inversion method by cold extrusion technique with precipitation immersion. The number of polymeric membranes available commercially is higher when compared to other materials, due mainly to its low cost, but the membranes from inorganic materials have been gaining greater attention due to properties such as thermal and chemical resistance. Thus, the following study aims to present the main characteristics of hollow fiber membranes of different materials, highlighting the main advantages, the methods of obtaining and applications.